Synthesis, Characterization, Antibacterial Evaluation, and Enzyme Inhibition Activity of a Novel Nitrogen-containing Heterocyclic Sulfonamide - Kong, Jingyao; Zhang, Xue; Xuan, Guangshan (Letters in Drug Design & Discovery, 2024)
IntroductionNovel sulfonamides containing pyrazole and 1,2,3-triazole were synthesized, and their inhibitory effects on six common pathogenic bacteria and COX-2 were investigated to screen new sulfonamides antimicrobial agents and COX-2 inhibitors with better effects.MethodsThe compounds with bacteriostatic effect were screened by using the ring of inhibition method and MTT chromogenic method, and the mechanism of bacteriostatic inhibition and description of bacteriostatic effect of the synthesized compounds were investigated with the aid of MOE molecular docking simulation and Gaussian molecular weighting calculations. The in vitro inhibitory effect of the synthesized compounds on COX-2 was studied using the phenylmethyl acetate color development method.ResultsThe results of bacterial inhibition experiments revealed that compounds 11d and 11e had better inhibition effects on pathogenic bacteria, especially on C. albicans, essentially the same as that of the positive control, FLUCZ. The compounds 4f, 7b, and 11c had the best inhibitory effect by COX-2 in vitro inhibition experiments, especially 11c, which had a better inhibitory effect than the positive control acetazolamide.ConclusionA series of derivatives obtained by introducing pyrazole and 1,2,3-triazole ring into sulfonamides have good bacteriostatic and COX-2 inhibition effects and have the potential to be developed as novel antimicrobial agents and enzyme inhibitors.
Keywords: Sulfonamide